Symmetry-mode analysis for intuitive observation of structure–property relationships in the lead-free antiferroelectric (1−x)AgNbO(3)–xLiTaO(3) - Lu, Teng (International Union of Crystallography, 2019)

(untitled) (IUCrJ)
Functional materials are of critical importance to electronic and smart devices. A deep understanding of the structure–property relationship is essential for designing new materials. In this work, instead of utilizing conventional atomic coordinates, a symmetry-mode approach is successfully used to conduct structure refinement of the neutron powder diffraction data of (1−x)AgNbO(3)–xLiTaO(3) (0 ≤ x ≤ 0.09) ceramics. This provides rich structural information that not only clarifies the controversial symmetry assigned to pure AgNbO(3) but also explains well the detailed structural evolution of (1−x)AgNbO(3)–xLiTaO(3) (0 ≤ x ≤ 0.09) ceramics, and builds a comprehensive and straightforward relationship between structural distortion and electrical properties. It is concluded that there are four relatively large-amplitude major modes that dominate the distorted Pmc2(1) structure of pure AgNbO(3), namely a Λ3 antiferroelectric mode, a T4+ a (−) a (−) c (0) octahedral tilting mode, an H2 a (0) a (0) c (+)/a (0) a (0) c (−) octahedral tilting mode and a Γ4− ferroelectric mode. The H2 and Λ3 modes become progressively inactive with increasing x and their destabilization is the driving force behind the composition-driven phase transition between the Pmc2(1) and R3c phases. This structural variation is consistent with the trend observed in the measured temperature-dependent dielectric properties and polarization–electric field (P-E) hysteresis loops. The mode crystallography applied in this study provides a strategy for optimizing related properties by tuning the amplitudes of the corresponding modes in these novel AgNbO(3)-based (anti)ferroelectric materials.